Interactive Powerpoint Media in Grade IV Elementary School - Al Fajar, Beny; Mayar, Farida (LPPM Undiksha, 2023)
The teacher as a facilitator must be able to present interesting material and learning for students. There are still many teachers who have not used learning tools that can assist teachers in conveying learning to students which can cause the learning process to be less than optimal. The media that will be used will make students more active in the learning process. One example of learning media that can be used by teachers is multimedia using Powerpoint. This research aims to develop interactive PowerPoint media for thematic learning in grade IV elementary school. This study uses research and development (R&D) methods using the 4D models. Data collection in this study used a questionnaire to determine the validity test and practicality test of the media. The effectiveness test is done by testing. The expert's validation on the material, media, and language aspect scored in Very Valid category. The results of the practicality test by the teacher obtained score in Very Practical category, and results of practicality test by students obtained score Very Practical category. The results of effectiveness test on aspect knowledge with the pretest at elementary school obtain very good predicate. Assessment of skills aspects at elementary school found Very Good predicate. From the research can be concluded that interactive PowerPoint media in class IV of elementary school is practical and effective for use in class IV of elementary school.